2015
DOI: 10.1002/ps.3992
|View full text |Cite
|
Sign up to set email alerts
|

Study of the long-distance migration of small brown planthoppersLaodelphax striatellusin China using next-generation sequencing

Abstract: The vector that caused rice stripe disease in the north-east of China was an immigrant population; however, the population may be formed from several groups from different areas, such as Jiangsu and Shandong provinces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Pairwise F ST values computed over mitochondrial COI and COII gene sequence and 13 microsatellite loci were very low, ranging from −0.017 to 0.027, with an average F ST of 0.006, and not detect significant genotypic differentiation between any pairwise populations (Sun et al, ). Zheng et al () reported that there was a certain gene flow among different populations, and the migration of insect pests accelerated the gene flow and increased the heterozygosity of SBPH populations, which were consistent with our findings. Overall, there was a relatively strong level of gene flow among populations in different climate zones, and the pairwise F ST values between the populations varied from 0.056 to 0.092, suggesting that there is a lack of strong differentiation between MTZ, STZ and WTZ groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Pairwise F ST values computed over mitochondrial COI and COII gene sequence and 13 microsatellite loci were very low, ranging from −0.017 to 0.027, with an average F ST of 0.006, and not detect significant genotypic differentiation between any pairwise populations (Sun et al, ). Zheng et al () reported that there was a certain gene flow among different populations, and the migration of insect pests accelerated the gene flow and increased the heterozygosity of SBPH populations, which were consistent with our findings. Overall, there was a relatively strong level of gene flow among populations in different climate zones, and the pairwise F ST values between the populations varied from 0.056 to 0.092, suggesting that there is a lack of strong differentiation between MTZ, STZ and WTZ groups.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, some other researchers revealed the long‐distance migration of SBPH in China use the SLAF‐seq technology. They detected 2,572 single nucleotide polymorphisms (SNPs) among 14 SBPH populations, which were collected from six provinces from April to June in 2013 (Zheng et al, ). In contrast, in the present study, we also investigated the genetic diversity and population genetic structure of SPBH populations using the highly density SNP markers covering the whole genome, we detected more reliable SNPs among 27 SBPH populations (32,556 SNPs), which were collected from 13 provinces, covering three climatic regions in 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLAF-seq is a high-throughput, high-accuracy, and low-cost method with short cycles, and has been used for molecular breeding and analysis of germplasm resources (Huang et al, 2016). SLAF-seq does not depend on a reference genome sequence and is particularly useful for species the lack an assembled reference genome (Sun et al, 2013), because it is possible to perform polymorphism analysis and develop molecular markers directly from the sequence data provided by SLAF-seq (Zheng et al, 2016). Given these advantages, SLAF-seq has been used for rapid mass discovery of SNP markers for polymorphism analysis, system evolution, and germplasm resource identification (Chen et al, 2013; Zhang et al, 2013; Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al . (2015) also found high level of genetic differences among fourteen overwintering SBPH populations in China by using SNPs. However, these results were not consistent with some other findings.…”
Section: Discussionmentioning
confidence: 87%